Between Efficiency and Empathy: Evidence of Ethical Ambivalence and the Residual Moral Subject in AI-Mediated Decision-Making - Aljula Gjeloshi; Anila Boshnjaku; Ledia Thoma (European Scientific Journal, ESJ, 2026)
The rapid integration of artificial intelligence (AI) into domains involving ethical judgment has generated renewed concern about the status of human moral agency. While much of the existing literature focuses either on technical optimization or normative prescriptions, fewer studies empirically investigate how human subjects themselves perceive moral responsibility under algorithmic mediation. This article presents an empirical–theoretical analysis of moral ambivalence in the age of AI, drawing on survey data (N = 146) collected among university students. The findings suggest that contemporary subjects neither fully reject nor uncritically accept AI as a moral authority. Instead, they occupy an intermediate position characterized by ethical ambivalence: technical efficiency increasingly competes with empathy, contextual judgment, and personal responsibility. We argue that this condition gives rise to a “residual moral subject,” whose agency is not eliminated but progressively reshaped under algorithmic governance.